Influence of Soil Fertility on Sesame (Sesamum Indicum L.) Under Repeated Water Stress - Vyas, S P; Garg, B K; Kathju, S; Lahiri, A N (Annals of Arid Zone, 2016)
Effects of one, two and three consecutive cycles of drought at the critical stage were studied in sesame crop grown under improved soil fertility (IF) and low soil fertility (LF) conditions. The dry matter production and seed yield of plants under one or two cycles of drought were significantly more under IF than under LF conditions notwithstanding the fact that plant RT % and diffusive resistance indicated relatively more water stress in the former than in the latter condition. This advantage was, however, lost under three cycles of drought. IF-plants under one or two cycles of drought had higher absolute nitrogen content which declined in the third cycle. Improved soil fertility generally increased both oil content of seeds and oil yield per plant. Droughts marginally increased the oil content of seeds but reduced the oil yield per plant.